The effect of concentration on particle settling in the Minas Basin, Nova Scotia. (1st July 2021) - Law, B.A.; Milligan, T.G.; Hill, P.S.; Bugden, G.L.
Abstract: In the hyper-tidal Minas Basin located in the upper Bay of Fundy, Canada, the concentration of total suspended matter increases by an order of magnitude in winter as material from the expansive tidal flats is remobilized and storms increase cliff erosion. Tripods with a digital floc camera, LISST 100X Type B, optical backscatter sensors, settling velocity camera, ADCP and an in-situ water filtration system were deployed during winter and summer conditions to examine how this variation in concentration affects particle packaging and settling. In winter, the higher concentration leads to rapid formation of large, low density flocs with lower settling velocities during the brief periods of low stress between ebb and flood. In summer, the material in suspension is dominated by small aggregates with higher excess densities and higher settling velocities. After a 70 mm rainfall event, flocs with lower density, and lower settling velocities appear again. Flocculation rate increases with concentration leading to the rapid formation of flocs in winter. However, stresses are high, so sediment remains mobile in winter. In the transition from winter to summer concentration is initially high, floc formation and settling is rapid, and wave energy is reduced allowing material to accumulate on the flats. In summer, the concentration of the sediment remaining in suspension is too low for flocs to form and aggregates dominate the population of particles suspended by the tide. Only when an input of new sediment occurs do new flocs form. Highlights: TSM in the hyper-tidal Minas Basin varies by an order of magnitude between winter and summer. The dependence of flocculation on concentration is clearly demonstrated by the introduction of fine-grained sediment in winter and after a summer rainfall event. The term aggregate is used to describe an association of small particles forming a larger particle with low Sauter diameter that are resistant to break up. Sauter diameters of particles are highest during peak flow in summer. The settling velocity of aggregates is usually greater than flocs of equal size due to their higher density and tighter packaging.